MRI in Chronic Aortic Dissection: A Systematic Review and Future Directions - Sherrah, Andrew G.; Grieve, Stuart M.; Jeremy, Richmond W.; Bannon, Paul G.; Vallely, Michael P.; Puranik, Rajesh (Frontiers in Cardiovascular Medicine, 2015)
The acute event of thoracic aortic dissection carries with it high mortality and morbidity. Despite optimal initial surgical or medical management strategies, the risk of further complications in the long term, including aneurysmal dilatation and false lumen expansion, are not insignificant. Adequate follow-up of such conditions requires dedicated imaging where relevant prognostic indicators are accurately assessed. We perform a systematic review of the literature and report the current evidence for the use of magnetic resonance imaging (MRI) in assessment of chronic aortic dissection. We then make a comparison with traditional imaging modalities including computed tomography (CT) and echocardiography. We discuss new ways in which MRI may extend existing aortic assessment, including identification of blood-flow dynamics within the true and false lumen using phase contrast (PC) imaging.